(untitled) (Latin American Journal of Sedimentology and Basin Analysis, 2024)
The input of large volume of volcaniclastic sediments causes significant changes and imbalances in natural systems, with the consequent readjustment of depositional environments. In fluvial systems, it can affect the hydrogeomorphology, sedimentation, composition of detritus, soil features and ecosystems. Consequently, the changes detected in the sedimentary record are usually linked with volcaniclastic sediment supply, mainly in near vent positions as aprons. In this context, a specific Cretaceous stratigraphic interval of the Somuncurá-Cañadón Asfalto Basin, Argentina, offers the possibility of testing the temporal evolution of a fluvial system to a large influx of volcaniclastic material from a distant source. Particularly, we analyzed the upper Bardas Coloradas and Puesto La Paloma Members, which belong to the Los Adobes and Cerro Barcino Formations respectively, in Los Chivos hill and surrounded area. The goal of this contribution was to evaluate in detail the paleoenvironmental evolution registered in these units, as well as the link with all allocyclic controls on sedimentation. Seven facies associations were defined including low sinuosity fluvial channel (FA1), meandering-like crevasse channel (FA2), splay (FA3), distal floodplain (FA4), aeolian (FA5), sheet-floods (FA6), and feeder channel (FA7). They were positioned into three informal stratigraphic intervals denominated A to C in chronological order of deposition. The stratigraphic interval A (upper Bardas Coloradas Member, 35 m thick) includes low sinuosity fluvial channels which transported a permanent sandy bedload towards the NW; and vegetated floodplain zones characterized by the presence of meandering-like crevasse channels, splays and shallow lakes or ponded zones. The stratigraphic interval B (lower Puesto La Paloma Member, 11-16 m thick) records a volcaniclastic-rich aeolian system composed of 2D aeolian dunes that migrated towards SE and were spatially related to wet- and dry-interdune zones where the sedimentation mostly occurred from subaqueous and subaerial settling of suspended volcaniclastic sediments, respectively. The stratigraphic interval C (upper Puesto La Paloma Member, 6-18 m thick) registers volcaniclastic-rich fluvial sedimentation characterized by unconfined flows, which were sediment-laden or diluted, and showing lateral relationships with ponded areas. Locally, there was a feeder channel that transported volcaniclastic gravels towards the NW. The assessment of allocyclic controls suggests that the volcaniclastic sediment supply governed the changes in the depositional system without important influence of tectonic activity, climatic changes, eustatic sea-level modifications and basement morphology.